Financial literacy and intra-household decision making: Evidence from Rwanda - Antonia Grohmann; Annekathrin Schoofs (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Research has consistently shown that women's involvement in household decision making positively affects household outcomes such as nutrition and education of children. Is financial literacy a determinant for women to participate in intra-household decision making? Using data on savings groups in Rwanda, we examine this relationship and show that women with higher financial literacy are more involved in financial and expenditure decisions. Instrumental Variable estimations confirm a causal link. For this reason, we perform a decomposition analysis breaking down the gender gap in financial literacy into differences based on observed sociodemographic and psychological characteristics and differences in returns on these characteristics. Our results show high explanatory power by education, happiness, symptoms of depression, and openness, but also suggest that a substantial fraction can be explained by differences in returns. We argue that this results from a strong role of society and culture.
Keywords: D14; J16; G02; 330; financial literacy; women empowerment; intra-household decision making